Peran Kemitraan Agribisnis Koperasi Eptilu Dalam Mendukung Pemberdayaan Petani Di Kabupaten Garut Jawa Barat - Putra, Rizki Aditya; Kurniasih, Dedeh; Martina, Martina (Jurnal Respon Komunitas dan Pemberdayaan, 2025)
Eptilu Cooperative was initiated by millennial farmers in Cigedug Village, Garut Regency, West Java, which aims to empower farmers and increase agricultural productivity through mutually beneficial partnerships. This study aims to identify the role of agribusiness partnership of Eptilu Cooperative in Garut Regency, West Java. The research was conducted at Eptilu Cooperative in Garut, West Java with the respondents were 3 administrators and 24 active members who were directly involved in business management. The data used in the research are primary data and secondary data. Primary data obtained from in-depth interviews using an interview guide and secondary data obtained through Eptilu cooperative profile data, Eptilu cooperative materials, and data from the Central Bureau of Statistics. to answer the objectives of the data were analyzed descriptively qualitative. The results of the study explain that there are six roles of the Eptilu Cooperative agribusiness partnership in supporting farmer empowerment in Garut Regency, West Java, namely the role of access to production inputs for farmers, the role of access to markets, capacity building and technology, the role in access to capital and financing for farmers, the role of strengthening the agribusiness value chain, and the role in empowering small farmers.